International Summit on Laparoscopic Pancreatic Resection (ISLPR) "Coimbatore Summit Statements". (March 2018) - Palanivelu, Chinnusamy; Takaori, Kyoichi; Abu Hilal, Mohammad; Kooby, David A.; Wakabayashi, Go; Agarwal, Anil; Berti, Stefano; Besselink, Marc G.; Chen, Kuo Hsin; Gumbs, Andrew A.; Han, Ho-Seong; Honda, Goro; et al.
Abstract: The International Summit on Laparoscopic Pancreatic Resection (ISLPR) was held in Coimbatore, India, on 7th and 8th of October 2016 and thirty international experts who regularly perform laparoscopic pancreatic resections participated in ISPLR from four continents, i.e., South and North America, Europe and Asia. Prior to ISLPR, the first conversation among the experts was made online on August 26th, 2016 and the structures of ISPLR were developed. The aims of ISPLR were; i) to identify indications and optimal case selection criteria for minimally invasive pancreatic resection (MIPR) in the setting of both benign and malignant diseases; ii) standardization of techniques to increase the safety of MIPR; iii) identification of common problems faced during MIPR and developing associated management strategies; iv) development of clinical protocols to allow early identification of complications and develop the accompanying management plan to minimize morbidity and mortality. As a process for interactive discussion, the experts were requested to complete an online questionnaire consisting of 65 questions about the various technical aspects of laparoscopic pancreatic resections. Two further web-based meetings were conducted prior to ISPLR. Through further discussion during ISPLR, we have created productive statements regarding the topics of Disease, Implementation, Patients, Techniques, and Instrumentations (DIPTI) and hereby publish them as "Coimbatore Summit Statements".